PENGARUH VARIABEL MAKRO EKONOMI TERHADAP RETURN SAHAM SYARIAH DI INDONESIA - Helvoni Mahrina (Jurnal Ilmu Akuntansi, 2020)
This study aims to determine empirical evidence of macroeconomic variables, foreign exchange rates, inflation, gross domestic product on sharia stock returns. This study uses multiple regression analysis. The results obtained include. 1. Changes in exchange rates have a significant negative effect on returns on Islamic stocks. 2. Changes in inflation have a significant positive effect on returns on Islamic stocks. 3. Changes in GDP do not have a significant positive effect on returns on Islamic stocks.